Weed control through crop rotation and alternative management practices - Böhm, Herwart (Julius-Kühn-Archiv, 2014)
Economic as well as agricultural and socio-political changes have an impact on crop management and thus also on crop rotation design and the related effects on the weed flora. Likewise other changes in cultivation such as reduced tillage practices, earlier sowing date, etc. cause an increase in weed infestation resp. an increased use of herbicides and if so contribute to herbicide resistance. The positive effects of crop rotation, but also of alternative management practices such as choice of varieties, catch crops, mixed cropping, green chop, and the share of predators, as well as methods of direct non-chemical weed control are presented and discussed for both, conventional and organic farming. If alternative management methods should be more practiced, especially trade-offs need to be broken, or incentives be offered.